Analysis of student errors based on newman's error analysis in terms of gender - Gestikatama, Elvindi; Hamidah, Dewi; Hidayah, Noer (LP3M Universitas Islam Zainul Hasan Genggong, 2024)
This research was conducted so that educators can find out the location of student errors. In addition to these factors, there are many other factors that influence student errors in answering math story questions, one of which is the gender factor. The analysis used to find out what types of mistakes students made, here the researcher uses Newman's procedure. The type of research used in this research is descriptive qualitative research. The research subjects were 31 students of class XI Madrasah Aliyah for the test. Then in the interview 6 subjects (3 women and 3 men) were taken representing each category of high, medium, low for interviews. Subjects were selected through a short test given by the researcher, the results of the previous test scores and discussion with the Mathematics Teacher of the class. The results of the study showed that female students made more mistakes in the completion process error indicator. Then in the male category, they made more mistakes in the final answer writing indicator. When viewed from the many types of errors of male and female students, a conclusion can be drawn that male subjects are slightly superior in solving math problems than female subjects. This is because men have better mechanical and mathematical abilities but women are also more effective in terms of accuracy and accuracy in solving mathematical problems.